Peran Produktif Buruh Tani Perempuan di Desa Mranggon Lawang Kecamatan Dringu Kabupaten Probolinggo - Dyah Ayu Safira (Fakultas Ekonomi dan Bisnis, 2025)
The role of women in families has shifted from being solely housewives to becoming individuals who contribute to the family economy, as seen in Mranggon Lawang Village, Dringu Sub-district, Probolinggo Regency. Based on 2025 Disdukcapil data, 678 women are recorded as farm laborers. This study aims to describe the productive role of female farm laborers using a descriptive qualitative method. Participants were selected through a snowball sampling technique, with data collected through interviews and documents, and analyzed using data reduction, data display, and conclusion drawing. The results show that female farm laborers play a significant role in agricultural activities, both in daily work (07.00–11.00) and in piece-rate work (12.00–15.00), earning an average wage of around Rp1,000,000 per month. It can be concluded that the productive role of female farm laborers not only supports agricultural activities but also makes a real contribution to the family economy through their income.
Reaploud Repository Hasyim April 2026
Keywords: female agricultural laborers; productive role